Numerical investigation of critical range for the occurrence of secondary peaks in the Nusselt distribution curve - Mohammed Umair, Siddque; Alrobaian, Abdul Rahman; Khan, Sher Afghan; Gnanagonda Kashinath, Marthande; Rajesh, Patil (Penerbit Akademia Baru, 2018)
The study of heat transfer augmentation in micro/nano scale and electronic packaging systems are some of the paramount areas of impending universe. In such systems the cooling of the hot heat sinks is generally achieved through the impingement of air jet. In order to study the characteristic of heat dissipation rate, variation of Nusselt number versus radial distance over the target surface is investigated. The magnitude of Nusselt Number is found to decrease gradually with increase in the radial distance away from the jet. The record of Nusselt magnitude over the radial distance is accomplished through computation using ANSYS CFX 14.5. A 2-D axis-symmetric model consisting of nozzle and target surface with discrete meshing is solved using an appropriate turbulence model, in order to develop the flow regime and record the necessary heat interactions. As far as the transition and intermediacy in flow structure at the target surface due to the un-predicted transport of shear stress is concerned, SST along with Gamma – Theta turbulence model is solved simultaneously in order to incorporate these phenomena.. The occurrence of such secondary peaks increases the heat transfer rate. Looking into the light of research area in determining the exact cause and the intervening range for the occurrence of such peaks, the current research focuses over the determination of the critical range within which the secondary peaks exists. This critical range comprises of multiple of jet to the target spacing and diameter-based Reynolds number and the corresponding critical range is between 2205 and 26, 46, 000. Not only that the velocity contour of the flow regime is mapped for the sets of parameters within the critical range. An empirical correlation for the area averaged Nusselt number terms of Reynolds number and jet to the target spacing being is proposed. This correlation improvises the calculation of the magnitude of area.